SYSTEM THINKING IN SOCIAL SYSTEM MODELLING - Šanda Martin; Křupka Jiří (Oeconomica, 2015)
This article deals with selected quality of life (QL) evaluations analysis done by means of System Thinking (ST). This evaluation is executed by using various indicators developed by the Economist Intelligence Unit Limited, by Eurofound Foundation and by the Organisation for Economic Cooperation and Development. The relevant case study works with data that are available for individual Visegrad Four (V4) countries. For these countries, values of partial indicators are discussed in relation with: the EU average value, the dynamic of these indicators for the given years and the utilization of objective and subjective indicators for the complex QL evaluation.
Systémové myšlení v modelování sociálního systému
Keywords: Evaluation; Indicators; Quality of life; System thinking; Hodnocení; indikátory; kvalita života; systémové myšlení